A biorefinery from Nannochloropsis sp. microalga – Extraction of oils and pigments. Production of biohydrogen from the leftover biomass - Nobre, Beatriz P. (2013)
The microalga Nannochloropsis sp. was used in this study, in a biorefinery context, as biomass feedstock for the production of fatty acids for biodiesel, biohydrogen and high added-value compounds. The microalgal biomass, which has a high lipid and pigment content (mainly carotenoids), was submitted to supercritical CO2 extraction. The temperature, pressure and solvent flow-rate were evaluated to check their effect on the extraction yield. The best operational conditions to extract 33 glipids/100 gdry biomass were found to be at 40 °C, 300 bar and a CO2 flow-rate of 0.62 g/min. The effect of adding a co-solvent (ethanol) was also studied. When supercritical CO2 doped with 20% (w/w) ethanol was used, it was possible to extract 45 glipids/100 gdry biomass of lipids and recover 70% of the pigments. Furthermore, the remaining biomass after extraction was effectively used as feedstock to produce biohydrogen through dark fermentation by Enterobacter aerogenes resulting in a hydrogen production yield of 60.6 mL/gdry biomass.